ONLINE LEARNING DURING THE COVID-19 PANDEMIC: IMPLEMENTATION IN SMP NEGERI 1 TENJO - Istikomah, Dian; Nurmayasari, Eva (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
This study aims to determine the implementation of online learning carried out at the junior high school level, in SMP NEGERI 1 TENJO, Bogor. The Covid-19 pandemic condition has an impact on the learning patterns that teachers can apply during the Covid-19 pandemic, namely online learning by considering health and safety aspects. This research is a quantitative descriptive study that focuses on the implementation of online-based learning processes and media preferences that are preferred by students in online learning. The results of this study indicate that students do not like online learning, but students prefer face-to-face learning rather than online systems. However, during online learning, 47.6% of students tend to prefer using WhatsApp as a learning tool because it is easy to use and low cost. Then 45.2% of students like learning using google meet. However, during online learning there are several obstacles experienced by students and teachers in online teaching and learning activities, namely unsupportive signals and additional internet quota fees. What's more, when learning is more, there are still some students who don't have gadgets to do learning.